Child personality facets and overreactive parenting as predictors of aggression and rule-breaking trajectories from childhood to adolescence. (22nd July 2015) - Becht, Andrik I.; Prinzie, Peter; Deković, Maja; van den Akker, Alithe L.; Shiner, Rebecca L.
Abstract: This study examined trajectories of aggression and rule breaking during the transition from childhood to adolescence (ages 9–15), and determined whether these trajectories were predicted by lower order personality facets, overreactive parenting, and their interaction. At three time points separated by 2-year intervals, mothers and fathers reported on their children's aggression and rule breaking ( N = 290, M age = 8.8 years at Time 1). At Time 1, parents reported on their children's personality traits and their own overreactivity. Growth mixture modeling identified three aggression trajectories (low decreasing, high decreasing, and high increasing) and two rule-breaking trajectories (low and high). Lower optimism and compliance and higher energy predicted trajectories for both aggression and rule breaking, whereas higher expressiveness and irritability and lower orderliness and perseverance were unique risk factors for increasing aggression into adolescence. Lower concentration was a unique risk factor for increasing rule breaking. Parental overreactivity predicted higher trajectories of aggression but not rule breaking. Only two Trait × Overreactivity interactions were found. Our results indicate that personality facets could differentiate children at risk for different developmental trajectories of aggression and rule breaking.